IMPACT OF TELEPRESENCE OF HOTEL WEBSITES ON BEHAVIORAL INTENTION OF INDIAN CONSUMERS - Khandelwal, Utkal; Sant, Tatavarty Guru (International Journal of Psychosocial Rehabilitation, 2020)
Hotel industry and booking of the same are experience products where customers have to judge the services of hotel through its website. Hence, hotel website becomes an essential to book and use it according to user’s usage. The purpose of this research is to discern the background of telepresence by examining variables such as sensory, emotional and cognitive attributes. In addition this research is also an attempt to measure the impacts of telepresence on behavioral intentions of customers regarding hotel websites. Theoretical framework to measure the impact of telepresence on the behavioral intention of the customers has been developed and data have been collected through online survey. Multiple regression technique has used to analyze the data. Finding established that telepresence leads to positive behavioral intention among customers. However sensory attributes found insignificant in forming positive behavioral intention. Telepresence plays a prominent role in encouraging and upholding consumer usage of hotel’s website and also play a catalyst role in information searching and decision making.